Entire solutions of the spruce budworm model - Lina Wang (Advances in Difference Equations, 2018)
Abstract This paper is concerned with the entire solutions of the spruce budworm model, i.e., solutions defined for all (x,t)∈R2 $(x,t)\in \mathbb{R}^{2}$. Using the comparison argument and sub-super-solution method, three types of the entire solutions are obtained, and each one of them behaves like two traveling fronts that come from both sides of the real axis and mix.